IBNU SINA: PEMIKIRAN FISAFATNYA TENTANG AL-FAYD, AL-NAFS, AL-NUBUWWAH, DAN AL-WUJÛD - Nur, Abdullah (Hunafa: Jurnal Studia Islamika, 2009)
One of the well-known Islamic philosophers in Islamic and western countries is Ibnu Sina. In  Western countries, he is known as Avicenna. Ibnu sina (370H/980M) is not only a great philosopher but  also a great scientist whose researches have been quoted many other scientists in the field of medicine until this modern era. He had contributed to development of philosophy and science since middle age in order to establish perfect philosophy system. He gained success in combining Aristotle thought, Plato and Neo-Platonism thought.Kata Kunci: Ibnu Sina, filsafat, al-fayd, al-nafs, al-wujûd, jiwa, akal